Prevalence of sleepiness while driving four-wheel motor vehicles in Fiji: a population-based survey (TRIP 9). Issue 4 (15th January 2013) - Herman, Josephine; Ameratunga, Shanthi N; Wainiqolo, Iris; Kafoa, Berlin; Robinson, Elizabeth; McCaig, Eddie; Jackson, Rod
Abstract : Introduction: Sleepiness has been shown to be a risk factor for road crashes in high-income countries, but has received little attention in low- and middle-income countries. We examined the prevalence of sleepiness and sleep-related disorders among drivers of four-wheel motor vehicles in Fiji. Method: Using a two-stage cluster sampling roadside survey conducted over 12 months, we recruited a representative sample of people driving four-wheel motor vehicles on the island of Viti Levu, Fiji. A structured interviewer-administered questionnaire sought self-report information on driver characteristics including sleep-related measures. Results: The 752 motor vehicle drivers recruited (84% response rate) were aged 17–75 years, with most driving in Viti Levu undertaken by male subjects (93%), and those identifying with Indian (70%) and Fijian (22%) ethnic groups. Drivers who reported that they were not fully alert accounted for 17% of driving, while a further 1% of driving was undertaken by those who reported having difficulty staying awake or feeling sleepy. A quarter of the driving time among 15–24-year-olds included driving while sleepy or not fully alert, with a similar proportion driving while chronically sleep deprived (ie, with less than five nights of adequate sleep in the previous week=27%). Driving while acutely or chronically sleep deprived was generally more common among Fijians compared with Indians. Conclusions: Driving while not fully alert is relatively common in Fiji. Sleepiness while driving may be an important contributor to road traffic injuries in this and other low- and middle-income countries.